A detailed seabed signature from Hurricane Sandy revealed in bedforms and scour. (3rd October 2013) - Trembanis, Arthur; DuVal, Carter; Beaudoin, Jonathan; Schmidt, Val; Miller, Doug; Mayer, Larry
Abstract : [1] On 30 October 2012, Hurricane Sandy made landfall near Brigantine New Jersey bringing widespread erosion and damage to the coastline. We have obtained a unique set of high‐resolution before and after storm measurements of seabed morphology and in situ hydrodynamic conditions (waves and currents) capturing the impact of the storm at an inner continental shelf field site known as the "Redbird reef". Understanding the signature of this storm event is important for identifying the impacts of such events and for understanding the role that such events have in the transport of sediment and marine debris on the inner continental shelf. As part of an ONR‐sponsored program designed to understand and characterize the ripple dynamics and scour processes in an energetic, heterogeneous inner‐shelf setting, a series of high‐resolution geoacoustic surveys were conducted before and after Hurricane Sandy. Our overall goal is to improve our understanding of bedform dynamics and spatio‐temporal length scales and defect densities through the application of a recently developed fingerprint algorithm technique. Utilizing high‐resolution swath sonar collected by an AUV and from surface vessel sonars, our study focuses both on bedforms in the vicinity of manmade seabed objects and dynamic natural ripples on the inner shelf in energetic coastal settings with application to critical military operations such as mine countermeasures. Key Points: Hurricane Sandy generated dramatic scour patterns on the seabed Repeated high‐resolution geophysical mapping revealed storm signature Large storm waves (> 7m) destroyed some artificial reef structures (subway cars)